ANALISIS PERAN LAPORAN PENELITIAN DALAM KOMUNIKASI ILMIAH MAHASISWA UNIVERSITAS NEGERI MEDAN - Aannisah Nadya Shafwah; Annarha Nayla; Eveline Stephani; Elly Prihasti Wuriyani; Melinda Isa Bella Tarigan; Shifa Syarlina Sari (STKIP Subang, 2026)
Research reports are one of the forms of scientific writing that play an important role in supporting scientific communication in higher education. Through research reports, students can systematically communicate research findings, ideas, and scientific information in accordance with academic writing standards. This study aims to analyze the role of research reports in the scientific communication of students at Universitas Negeri Medan. This study employed a quantitative descriptive approach using a survey method. Data were collected through a questionnaire distributed to 30 students of Universitas Negeri Medan who had experience in preparing research reports. The research instrument consisted of 20 statement items covering five indicators: research reports as a medium of scientific communication, development of academic writing skills, development of critical thinking skills, support for academic activities, and development of students’ scientific competence. The collected data were analyzed using descriptive percentage techniques. The results showed that research reports have a very significant role in supporting students’ scientific communication, with an average percentage score of 88.4%. The indicator of research reports as a medium of scientific communication obtained the highest percentage (90%), followed by support for academic activities (89%), development of academic writing skills (88%), development of students’ scientific competence (88%), and development of critical thinking skills (87%). These findings indicate that research reports function not only as a means of disseminating scientific information but also as a tool for enhancing academic writing skills, critical thinking abilities, and scientific competence among students. Therefore, research reports serve as an essential instrument in strengthening academic culture and improving the quality of scientific communication in higher education institutions.